Suplementação com doses crescentes de selênio associado à vitamina E no tratamento de bovinos com hematúria enzoótica - Moreira Júnior, Carlos Alberto (2023)
Enzootic bovine hematuria (EBH) is a clinical form of poisoning in cattle caused by the consumption of Pteridium sp. (bracken fern). This disease has a high prevalence in the south of the state of Espírito Santo, Brazil and has no treatment. However, supplementation using selenium (Se) and vitamin E has been shown to be viable. Thus, the aim of this work was to evaluate the effects of supplementation with increasing doses of selenium associated with vitamin E in cattle with enzootic hematuria, as well as to compare selenium levels in whole blood and blood serum and to evaluate the relative activity of the monoamine enzyme oxidase (MAO) in the serum of these animals. For this, 51 whole blood samples and 68 serum samples from 18 cattle with a clinical form of EBH were analyzed.The experimental design was a completely randomized design, with four groups distributed, namely: control group (saline solution), treatment group 1 (0.05 mg/Kg of Se), treatment group 2 (0.10 mg/kg of Se) and treatment group 3 (0.20 mg/Kg of Se), all groups received 500mg/animal of vitamin E in association. Parenteral supplementation was performed intramuscularly for 13 weeks. Biweekly evaluations were performed regarding the intensity of hematuria and weight gain, hematocrit, total plasma proteins (TPP), plasma fibrinogen, Se and relative MAO activity. For statistical analysis were used Kruskal Wallis and Friedman tests with a significance level of 5%, both followed by Dunn's multiple comparison test. It was found that there was no significant difference in weight between the different groups, but there was a reduction in weight over time in the control group. However, there was a significant difference in the intensity of hematuria in the treatment group 1 in relation to the control group after three weeks of supplementation, though, there was no significant difference in the intensity of hematuria over time. There was a significant increase in hematocrit in the treatment group 1 compared to the control group after seven weeks of supplementation, but there was no difference over time in each treatment. For PPT and Fb, no significant differences were observed either between treatments or in relation to time. Se levels were higher in treatment group 1, reaching the highest concentration at serum M8. Relative MAO activity did not differ between groups, but showed a significant reduction over time in each treatment. The supplementation of dairy cattle affected by EBH, using a dose of 0.05 mg/kg selenium associated with vitamin E, improved the clinical sign of hematuria and increased the hematocrit of the animals after three and seven weeks of supplementation, respectively. Serum proved to be the best place to measure Se and there was an increase in the concentration of this element in the eighth week of supplementation. In addition, there was a reduction in MAO activity that can be attributed to vitamin E supplementation, with no influence of different doses of Se.